Comparative Omics Analysis of Historic and Recent Isolates of Bordetella pertussis and Effects of Genome Rearrangements on Evolution - Dienstbier, Ana; Amman, Fabian; Petráčková, Denisa; Štipl, Daniel; Čapek, Jan; Zavadilová, Jana; Fabiánová, Kateřina; Držmíšek, Jakub; Kumar, Dilip; Wildung, Mark; Pouchnik, Derek; Večerek, Branislav (Emerging infectious diseases, 2021)
Despite high vaccination coverage, pertussis is increasing in many industrialized countries, including the Czech Republic. To better understand Bordetella pertussis resurgence, we analyzed historic strains and recent clinical isolates by using a comparative omics approach. Whole-genome sequencing showed that historic and recent isolates of B. pertussis have substantial variation in genome organization and form separate phylogenetic clusters. Subsequent RNA sequence analysis and liquid chromatography with mass tandem spectrometry analyses showed that these variations translated into discretely separated transcriptomic and proteomic profiles. When compared with historic strains, recent isolates showed increased expression of flagellar genes and genes involved in lipopolysaccharide biosynthesis and decreased expression of polysaccharide capsule genes. Compared with reference strain Tohama I, all strains had increased expression and production of the type III secretion system apparatus. We detected the potential link between observed effects and insertion sequence element-induced changes in gene context only for a few genes.
Keywords: Humans; Phylogeny; Proteomics; Pertussis Vaccine; pertusová vakcína; lidé; Bordetella pertussis; proteomika; pertuse; insertion sequence element; omics analysis; pathogen evolution; fylogeneze; pertussis; Czech Republic; whooping cough; Whooping Cough; Česká republika; bacteria; genomic rearrangements